SYSTEMATIC FAMILY APPROACH IN WORKING WITH PEOPLE WITH EATING DISORDERS (Annual of the Faculty of Philosophy in Skopje, 2019)
Eating disorders have been known since ancient times, but nowadays theyhave undergone many changes. The first records of eating disorders have been observedsince ancient times, with the Roman emperors, etc. There are written documentson the starvation and end of the menstrual cycle in nuns, since the ninth century.Seneca, for the then lifestyle, said: "People eat to repent and vomit in order to be ableto eat again." It essentially represents the difference in the way and style of life andtoday's diet, where the main goal is to reduce of body weight.Eating disorders indicate unhealthy eating habits, the attitude to food, andthe maintenance of body weight, and a common feature of all dietary disorders is theperception of the body's perception. Diseases of eating disorders are a significantpsychological, sociological and general health problem. The latest world research andtheir results show that it is necessary to invest on the prevention of these diseases,on the adequate training and education of parents in the formation of healthy eatinghabits among children, education of the medical personnel in early recognition andrisk detection, and later and diseases of eating disorders, education by schools andother professionals who have contact with the population at risk of developing a disorderin the diet. Adolescents represent the most at risk of developing a dietary disorderof any kind, as confirmed in the research. The influence of the modern way oflife, the influence of the media, peers, and the whole socio-cultural pressure on theperson, and many other external factors, encourage and increase the number of peoplewith eating disorders.
Keywords: EATING DISORDERS; ADOLESCENTS; PSYCHOTHERAPY